(untitled) (Palimpsesto, 2022)
The “Young People Building the Future” program seeks to train young people for the labor market and thereby reduce unemployment. The objective of this article is to analyze the results of the program. The hypothesis is that the program complies with training young people, however, it does not guarantee insertion in the labor market once the training process is finished. The methodology used is mixed: the objectives of the program and its rules of operation were reviewed, data was obtained from the beneficiaries and the tutors, and seventeen interviews were also carried out with the young people who participated. It concludes by proving the hypothesis and suggesting a review of the operation to avoid corruption.